Effect of permittivity on energy band diagrams of dielectric metamaterial arrays. Issue 1 (20th November 2012) - Hosseinzadeh, Arash; Semouchkina, Elena
Abstract Band diagrams of 2D arrays of dielectric rods are simulated at TE wave incidence in dependence on dielectric permittivity of rod material. It is shown that permittivity defines the variety of propagation modes corresponding to extreme energies of the lowest transmission bands because of interplay between Bragg and Mie resonances. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:134–137, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27219